Pemberdayaan Ibu Hamil Melalui Kelas Ibu Hamil Tentang Praktik Pola Makan, Pola Asuh dan Sanitasi di Desa Ujanmas Baru Tahun 2024 - Siti Fatimah; Umi Daimah; Rita Kamalia (Yayasan Daarul Huda Kruengmane, 2025)
A woman’s nutritional status must be prepared before and during pregnancy because it is an indirect factor that contributes to fetal growth and development. The prevention of stunting is focused on the first 1,000 days of life (from conception to a child’s second birthday), as this period is crucial in determining a child’s quality of life (Ministry of Health, 2018). Efforts that can be undertaken include improving nutritional status during adolescence, the preconception period, pregnancy, and early childhood. This also requires increasing government awareness and community participation through routine growth monitoring at Posyandu, improving healthy sanitation behavior and access to clean water, and ensuring the availability of nutritious and affordable food products (Sakti, 2020). Based on data obtained from the village midwife in Ujanmas Baru Village, most pregnant women do not know how to manage dietary patterns, parenting practices, and sanitation, even though these three factors are key efforts in preventing stunting in infants to be born. The target of this community service activity is pregnant women in Ujanmas Baru Village. The methods used include counseling and demonstrations on dietary patterns (Isi Piringku), parenting practices, and sanitation for pregnant women. These activities aim to increase the knowledge and skills of pregnant women regarding proper diet (Isi Piringku), parenting, and sanitation during pregnancy in order to prevent stunting early, starting from pregnancy. The expected outcomes are increased knowledge and skills of pregnant women in implementing appropriate dietary patterns (Isi Piringku), good parenting practices, and proper sanitation during pregnancy, as well as publication in a national journal.